Visual Status of Children with Down Syndrome. - Duckman, Robert H. (Optometry & Visual Performance, 2014)
Background: Children with Down syndrome (DS) are known to have a high prevalence of visual anomalies including strabismus, high refractive errors, Brushfield spots, nystagmus, keratoconus, and external pathologies such as blepharitis and conjunctivitis. These anomalies can impair children with DS from maximum functional capabilities. Methods: This study looks at 42 children from Stepping Stone Day School between the ages of 2.33 years and 5.17 years. All 42 children received a comprehensive visual evaluation. Testing included visual acuity (either forced preferential looking (FPL) or Lea Picture Cards), ocular motor status (motilities and cover test/Hirschberg test), dry and damp retinoscopy, and ocular health examination with dilation. Results: DS children showed a significantly higher prevalence than normal children of strabismus (43%), ocular-motor deficiencies (100%), decrease in visual acuity (31; 74% of the children had uncorrected visual acuity between 20/60 and <20/400), and high refractive errors (one third had hyperopia >+1.50, 23.81% had myopia > -1.00, and 28.57% had astigmatism > 1.00 diopter; one third had no significant refractive error). Conclusion: It is clear that children with DS should have annually thereafter.